Posterior reversible encephalopathy syndrome associated with use of Atezolizumab for the treatment of relapsed triple negative breast cancer. (2022) - Foulser, Peter F.G.; Senthivel, Nishanthi; Downey, Kate; Hart, Paul E.; McGrath, Sophie E.
Abstract: Posterior reversible encephalopathy syndrome (PRES) is a complex neurological disorder with multiple clinical manifestations including headaches, seizures, and altered mental status. It is associated with many conditions including malignancy and medications including chemotherapy and immunotherapy. We report the case of a 56-year old female with a history of advanced triple negative breast cancer treated with atezolizumab (a PD-L1 inhibitor), paclitaxel and ipatasertib (investigational AKT inhibitor), who developed hypertension, confusion, and imaging findings consistent with PRES.